Analysis of Competency, Integrity, And Capability on The Performance Of Information System Based Budget Planning - Muhammad Hatta; Angky Soedrijanto; Sri Rahayu (PT. BATARI EDU CALYA, 2025)
Budget planning in the Regional Government financial system currently centers on an information system that is directly connected to the central information system in Jakarta. The accuracy of planning depends on the ability of the planning apparatus so that the circulation of money transfers from the Center to the Regions runs smoothly. The research aims to examine the competency, integrity and capability factors of budget planners in terms of using the available information systems properly so that the financial transfer process for the Region runs smoothly. Qualitative descriptive research. Data was obtained from structured, repeated and in-depth interviews with selected respondents who had been determined. The interview results were compiled using a weighting technique to obtain numerical figures on a scale of 1-10. The number of respondents was 115 people from budget planners and officials at the Regional Apparatus Organization of Fakfak Regency. Based on the weight results, a gap analysis can be carried out which is displayed using spider web analysis. The research results show that the competency, integrity and capability of budget planners must be continuously improved through education and training. This is based on the many technical changes in the use of information systems which budget planners must know and master at all times